Annoyance Related to Wind Turbine Noise - PAWLACZYK-ŁUSZCZYŃSKA, Małgorzta; DUDAREWICZ, Adam; ZABOROWSKI, Kamil; ZAMOJSKA-DANISZEWSKA, Małgorzta; WASZKOWSKA, Małgorzta (Archives of Acoustics, 2014)
A questionnaire inquiry on response to wind turbine noise was carried out on 361 subjects living in the vicinity of 8 wind farms. Current mental health status of respondents was assessed using Goldberg General Health Questionnaire GHQ-12. For areas where respondents lived, A-weighted sound pressure levels (SPLs) were calculated as the sum of the contributions from the wind power plants in the specific area. Generally, 33.0% of respondents were annoyed outdoors by wind turbine noise at the calculated A-weighted SPL of 31–50 dB, while indoors the noise was annoying to 21.3% of them. The proportion of subjects evaluating the noise produced by operative wind turbines as annoying decreased with increasing the distance from the nearest wind turbine (27.6% at the distance of 400–800 m vs 14.3% at the distance above 800 m, p < 0.016). On the other hand, the higher was the noise level, the greater was the percentage of annoyed respondents (14.0% at SPL up to 40 dB vs 28.1% at SPL of 40–45 dB, p < 0.016). Besides noise and distance categories, subjective factors, such as general attitude to wind turbines, sensitivity to landscape littering and current mental health status, were found to have significant impact on the perceived annoyance. About 50% of variance in annoyance rating might be explained by the aforesaid subjective factors.